4
$\begingroup$

I am currently working on the proof of Theorem 3.1 in the book "Foundations of Machine Learning" (page 35, First edition), and there is a key trick used in the proof (equation 3.10 and 3.11):

$$\begin{align*} &E_{S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} g(z'_i)-g(z_i)\right]=E_{\boldsymbol{\sigma},S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} \sigma_i(g(z'_i)-g(z_i))\right] \\ &\text{where } {\Bbb P}(\sigma_i=1)={\Bbb P}(\sigma_i=-1)=\frac{1}{2} \end{align*}$$

It is also shown in the lecture pdf page 8 in this link: https://cs.nyu.edu/~mohri/mls/lecture_3.pdf

This is possible because $z_i$ and $z'_i$ can be swapped. My question is, why can we swap $z_i$ and $z'_i$? In the book, it says this is possible because "we are taking the expectation over all possible $S$ and $S'$, it will not affect the overall expectation." Unfortunately, I don't understand the meaning or intuition of this part.

Thank you very much for reading the question and for your time!

$\endgroup$

1 Answer 1

3
$\begingroup$

This requires hell of a derivation, but I liked the question :)

My question is, why can we swap $z_i$ and $z'_i$?

The key insight is that notation $S \sim \mathcal{D}^m$ is equivalent to $Z_1 \sim \mathcal{D}, \cdots, Z_m \sim \mathcal{D}$. This translates to $$E_{S,S'}[.]=E_{Z_1,\cdots,Z_m,Z'_1,\cdots,Z'_m}[.]$$ which remains the same by reordering the $Z$s.

Therefore the swap argument can be shown by

  1. Singling out an arbitrary term $k$ from $\sum_{i=1}^{m}$,
  2. Switching $E_{Z_k,Z'_k}$ to $E_{Z'_k,Z_k}$, and
  3. Renaming the variables.

That is, $$\begin{align*} &E_{S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} g(z'_i)-g(z_i)\right] \\ &\overset{\text{expand}}{=} E_{\color{blue}{Z_1,\cdots,Z_m,Z'_1,\cdots,Z'_m}}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} g(z'_i)-g(z_i)\right]\\ &\overset{\text{separate}}{=} E_{\cdots,Z_k,\cdots,Z'_k,\cdots}\left[\underset{g \in \mathcal{G}}{\text{sup}} \frac{1}{m}\left(\color{blue}{g(z'_k)-g(z_k)}+\sum_{i=1; \neq k}^{m} g(z'_i)-g(z_i)\right)\right] \\ &\overset{\text{switch}}{=} E_{\cdots,\color{blue}{Z'_k},\cdots,\color{blue}{Z_k},\cdots}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\left(g(z'_k)-g(z_k)+\sum_{i=1; \neq k}^{m} g(z'_i)-g(z_i)\right)\right] \\ &\overset{\text{reorder}}{=} E_{\cdots,Z'_k,\cdots,Z_k,\cdots}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\left(\color{blue}{-(g(z_k)-g(z'_k))}+\sum_{i=1; \neq k}^{m} g(z'_i)-g(z_i)\right)\right] (*) \end{align*}$$ Now by renaming $Z_k \leftrightarrow Z'_k$, and thus $z_k \leftrightarrow z'_k$ in $(*)$ we have: $$\begin{align*} &E_{S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} g(z'_i)-g(z_i)\right] \\ &\overset{\text{rename}}{=} E_{\cdots,\color{blue}{Z_k},\cdots,\color{blue}{Z'_k},\cdots}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\left(-(g(\color{blue}{z'_k})-g(\color{blue}{z_k}))+\sum_{i=1; \neq k}^{m} g(z'_i)-g(z_i)\right)\right]\\ &\overset{\text{collapse}}{=} E_{S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\left(-(g(z'_k)-g(z_k))+\sum_{i=1; \neq k}^{m} g(z'_i)-g(z_i)\right)\right]\\ \end{align*}$$

which corresponds to $\boldsymbol{\sigma}=(\sigma_1=1,\cdots,\sigma_k = -1,\cdots,\sigma_m=1)$.

We have proved this equality by switching the sign of arbitrary index $k$. Therefore, by defining $$f(\boldsymbol{\sigma}):=E_{S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} \sigma_i(g(z'_i)-g(z_i))\right]$$ we have shown that $$\forall \boldsymbol{\sigma_1}, \boldsymbol{\sigma_2},f(\boldsymbol{\sigma_1})=f(\boldsymbol{\sigma_2}).$$ For example: $$\begin{align*} f(\boldsymbol{1})&=f(\sigma_1=1,\cdots,\sigma_k=1, \cdots,\sigma_m=1)\\ &=f(\sigma_1=1,\cdots,\sigma_k=-1, \cdots,\sigma_m=1) \end{align*}$$ Knowing that there is $2^m$ equi-probable vectors $\boldsymbol{\sigma_i}$, we finally have $$\begin{align*} E_{S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} g(z'_i)-g(z_i)\right]&=f(\boldsymbol{1}) \\ &=\frac{1}{2^m} f(\boldsymbol{\sigma_1})+\cdots+\frac{1}{2^m}f(\boldsymbol{\sigma_{2^m}})\\ &=E_{\boldsymbol{\sigma}}[f(\boldsymbol{\sigma})] \\ &=E_{\boldsymbol{\sigma},S,S'}\left[\underset{g \in \mathcal{G}}{\text{sup}}\frac{1}{m}\sum_{i=1}^{m} \sigma_i(g(z'_i)-g(z_i))\right] \end{align*}$$ $\square$

$\endgroup$
1
  • 1
    $\begingroup$ Thank you so much for your time! Great explanation of what was happening in between equation 3.10 and 3.11. I really enjoyed going through the detailed derivations. $\endgroup$ Commented Apr 9, 2019 at 9:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.